How successful is color flow mapping and pulsed Doppler studies in predicting histologically confirmed benign and malignant adnexal masses in perimenopausal women - Gangopadhyay, Souptik; Chakraborty, Partha Sarathi; Singh, Archana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Adnexal masses in perimenopausal women presents a specific diagnostic challenge because benign masses outnumbers malignant masses. Majority of adnexal masses are benign but 25% are malignant. The objective of this study was to see the effectiveness of transvaginal colour Doppler in predicting malignancy in adnexal masses in perimenopausal women. Methods: Clinically detected adnexal masses were subjected to transabdominal ultrasound scan (for basic characterization of mass into solid, cystic, mixed) then transvaginal scan and neovascularization, resistivity index (RI) was measured. Subsequently all patients underwent laparotomy. Histopathological reports obtained, and correlation done between USG and histopathology. Results: Among cystic masses neovascularization was present in 4 cases, among them benign and malignant masses were equal in number. Among mixed masses neovascularization was present in 17 cases 9 were malignant 8 benign, among solid masses all cases where neovascularization was detected were malignant. Neovascularization was absent in 12 cystic masses and 11 mixed masses, and all were benign. Kappa value calculated for tumour status and neovascularization is 0.610 which is substantially agreement with neovascularization as predictor of malignancy. Sensitivity, specificity, positive predictive value and negative predictive value of neovascularization for cystic masses are 100, 85, 50, 100(%) respectively. Sensitivity, specificity, positive predictive value and negative predictive value of neovascularization for mixed masses are 100, 57.89, 52.94, 100(%) respectively. Sensitivity and positive predictive value of neovascularization for solid masses is 100(%). Sensitivity specificity positive predictive value and negative predictive value of RI for cystic masses: 100, 92.8, 66.6, 100 (%) respectively. Sensitivity specificity positive predictive value and negative predictive value of RI for mixed masses: 77.7, 89.4, 77.7, 89.4(%). Sensitivity positive predictive value of RI for solid masses 100%.ROC curve analysis shows cut off value for differentiating between benign and malignant masses is 0.4. Less than 0.4 has more chance of malignancy. Conclusions: Transvaginal Doppler ultrasound must be done preoperatively for adnexal mass characterization.